Recent Advances in QEPAS and QEPTS Based Trace Gas Sensing: A Review - Yufei Ma (Frontiers in Physics, 2020)
This invited review paper summarizes and discusses developments of QTF based state-of-the-art quartz-enhanced photoacoustic spectroscopy (QEPAS) and quartz-enhanced photothermal spectroscopy (QEPTS) gas sensing techniques over the past 3 years. Due to the merits of a high quality factor, a narrow resonance frequency band, a low cost, a small volume, and immunity to the laser wavelength, a QTF is widely used as a sensitive detector in sensing photoacoustic spectroscopy and photothermal spectroscopy based gas. The review also presents prospects in the development of QEPAS and QEPTS based gas sensing techniques.